Diagnosis of Internal Jugular Vein Septic Thrombophlebitis by Point-of-Care Ultrasound. Issue 10 (23rd October 2022) - Shah, Aalap; Moake, Matthew M.
Abstract: Septic thrombophlebitis represents a rare but serious collection of diseases, which carry a high risk of morbidity and mortality requiring prompt and aggressive treatment. Diagnosis centers on identification of thrombus along with clinical and microbiologic data. We present a case where point-of-care ultrasound was used to diagnose septic thrombophlebitis of the internal jugular vein and expedite appropriate therapy. We further review the technique and literature for ultrasound diagnosis of venous thrombosis and associated thrombophlebitis.